Effectiveness of a Self-Management Intervention to Promote an Active Lifestyle in Persons With Long-Term Spinal Cord Injury: The HABITS Randomized Clinical Trial. (December 2017) - Kooijmans, Hedwig; Post, Marcel W. M.; Stam, Henk J.; van der Woude, Lucas H. V.; Spijkerman, Dorien C. M.; Snoek, Govert J.; Bongers-Janssen, Helma M. H.; van Koppenhagen, C. F.; Twisk, Jos W.; ,; Bussmann, Johannes B. J.
Background . Most people with long-term spinal cord injury (SCI) have a very inactive lifestyle. Higher activity levels have been associated with health benefits and enhanced quality of life. Consequently, encouraging an active lifestyle is important and behavioral interventions are needed to establish durable lifestyle changes. Objective . The Healthy Active Behavioral Intervention in SCI (HABITS) study was aimed to evaluate the effectiveness of a structured self-management intervention to promote an active lifestyle in inactive persons with long-term SCI. Methods . This assessor-blinded randomized controlled trial was conducted at 4 specialized SCI units in the Netherlands. Sixty-four individuals with long-term SCI (>10 years), wheelchair-user and physically inactive, were included. Participants were randomized to either a 16-week self-management intervention consisting of group meetings and individual counseling and a book, or to a control group that only received information about active lifestyle by one group meeting and a book. Measurements were performed at baseline, 16 weeks, and 42 weeks. Primary outcome measures were self-reported physical activity and minutes per day spent in wheelchair driving. Secondary outcomes included perceived behavioral control (exercise self-efficacy, proactive coping), stages of change concerning exercise, and attitude toward exercise. Results . Mixed models analyses adjusted for age, sex, level of SCI, time since injury, baseline body mass index, and location did not show significant differences between the intervention and control groups on the primary and secondary outcomes ( P ≥ .05). Conclusions . A structured 16-week self-management intervention was not effective to change behavior toward a more active lifestyle and to improve perceived behavioral control, stages of change, and attitude.